A facile method to prepare noble metal nanoparticles modified Self-Assembly (SAM) electrode. Issue 1 (1st January 2018) - Liu, Feng; Huang, Long; Duan, Xiao; Li, Yun-yan; Hu, Jin-quan; Li, Bai-hui; Lu, Jun
ABSTRACT: Noble metal nanoparticles (NPs) modified electrodes have shown promising applications in the areas of catalysis, (electro)chemical analysis and biosensing due to their unique characters. In this paper, we introduced a so-called ligand exchange method to prepare self-assembly (SAM) electrode modified with noble metal nanoparticles. The noble metal nanoparticles protected by weakly adsorbed tetraoctylammonium bromide (TOAB) were synthesized firstly, then self-assembly (SAM) dithiol-modified Au electrode (Au-SHSAM ) was immersed into the solutions containing TOAB-protected nanoparticles. Due to the strong interaction between the dithiol groups on the electrode and noble metal nanoparticles, the weakly adsorbed TOAB on the surface of noble metal NPs were replaced by dithiol groups. As a result, the TOAB protected NPs were anchored on the Au-SHSAM template electrode surface by ligand exchange, obtaining noble metal NPs modified electrode with high quality and stability. By adjusting the soaking time, the coverage of nanoparticles on the Au-SHSAM electrode surface could be controlled. The morphology and distribution of noble metal NPs on Au-SHSAM surface was analysis by scanning tunneling microscope (STM), and their electrochemical property was studied by cyclic voltammetry (CV) in H2 SO4 solution. The approach is proved as a universal way to prepare noble metal NPs modified SAM electrode.